GOVERNANCE EVALUATION OF DRUG INSTALLATION IN THE PHARMACEUTICAL INSTALLATION WAREHOUSE OF THE SIMALUNGUN DISTRICT TRADING HOSPITAL, 2020 - Syarifuddin, Shofian; Frimpong Oppong, Richard; Tony Sohdin Martua Simanjuntak, Edwin; Hanindiya, Beta; Kurniawan, Hendri (Universitas Efarina, 2020)
The quality of services provided by the house greatly affects the image of the hospital and the satisfaction of patients who visit the hospital. One of the factors that plays a role in the quality of hospital services is the evaluation of the management of drug supplies in the hospital. Evaluation of drug supply governance is necessary to prevent drug shortages (stock out), drug excess (over stock), and drug vacancies in a limited manner. There has been a drug vacuum in the trading hospital due to an increase in the number of patients. The purpose of this study was to determine the evaluation of drug supply management in the Pharmacy Warehouse of the Trade Simalungun District Hospital. This type of research is descriptive research with an observational approach. In this study, there was a source of information, namely from the Head of the Pharmacy Installation. The results showed that the evaluation of drug supply management in the pharmaceutical warehouse of the Simalungun District Hospital of Commerce was quite effective, but there are several factors that can affect drug vacancies. This can be seen from several components of Input (especially the storage warehouse which is less representative), Process (inconsistency with the use of preparations, inaccurate planning, changing room temperatures affecting existing supplies, resulting in damaged and expired supplies) and Output. (As needed). It is expected that the Head of the Pharmacy Installation of the Simalungun District Hospital for Trade will pay more attention to the planning and procurement of drugs to minimize forgotten preparations and avoid expired drugs. The results showed that the evaluation of drug supply management in the pharmaceutical warehouse of the Simalungun District Hospital of Commerce was quite effective, but there are several factors that can affect drug vacancies. This can be seen from several components of Input (especially the storage warehouse which is less representative), Process (inconsistency with the use of preparations, inaccurate planning, changing room temperatures affecting existing supplies, resulting in damaged and expired supplies) and Output. (As needed). It is expected that the Head of the Pharmacy Installation of the Simalungun District Hospital for Trade will pay more attention to the planning and procurement of drugs to minimize forgotten preparations and avoid expired drugs. The results showed that the evaluation of drug supply management in the pharmaceutical warehouse of the Simalungun District Hospital of Commerce was quite effective, but there are several factors that can affect drug vacancies. This can be seen from several components of Input (especially the storage warehouse which is less representative), Process (inconsistency with the use of preparations, inaccurate planning, changing room temperatures affecting existing supplies, resulting in damaged and expired supplies) and Output. (As needed). It is expected that the Head of the Pharmacy Installation of the Simalungun District Hospital for Trade will pay more attention to the planning and procurement of drugs to minimize forgotten preparations and avoid expired drugs.